Aerogels: Tailor-made carriers for immediate and prolonged drug release - Smirnova, Irina; Suttiruengwong, Supakij; Arlt, Wolfgang (KONA Powder and Particle Journal, 2005)
The potential of inorganic polymeric materials - silica aerogels - as tailor-made drug carriers is discussed. It is shown that the dissolution rate of poorly soluble drugs can be significantly changed through the adsorption on silica aerogels. Adsorption takes place in supercritical CO2 and allows distribution of the drugs inside the aerogel matrix on the molecular level. The drug concentration in the aerogel is explicitly determined by the temperature, bulk concentration of the drug in the supercritical phase and the properties of the aerogel (density, pore size distribution and surface area). The release rate of the drug depends on the hydrophobicity of the aerogel. In the case of hydrophilic aerogels, an extremely fast release - even compared with nanocrystals - of drugs is achieved, which is especially advantageous for poorly water-soluble drugs. Hydrophobic aerogels exhibit a slower release which is governed by diffusion. In addition, the possibility of generating organic microparticles inside the pores of the aerogels by precipitation from supercritical solutions is discussed.
Keywords: Adsorption; Aerogels; Drug carriers; Supercritical fluid